Use matters an alternative history of architecture - Cupers, Kenny 1977- (Routledge, 2013)
"From participatory architecture to interaction design, the question of how design accommodates use is driving inquiry in many creative fields. Expanding utility to embrace people's everyday experience brings new promises for the social role of design. But this is nothing new. As the essays assembled in this collection show, interest in the elusive realm of the user was an essential part of architecture and design throughout the twentieth century. Use Matters is the first to assemble this alternative history, from the bathroom to the city, from ergonomics to cybernetics, and from Algeria to East Germany. It argues that the user is not a universal but a historically constructed category of twentieth-century modernity that continues to inform architectural practice and thinking in often unacknowledged ways"--
Includes bibliographical references and index
Keywords: Architecture and society / History; Functionalism (Architecture); ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Design, Drafting, Drawing & Presentation; Geschichte; Alternativgeschichte; Funktionalismus -- Architektur; Architekturtheorie; Aufsatzsammlung